Family problems - wife’s work - and its solution in the light of Maqasid Shariah - Muhammad Husni, Ahmad; Nasohah, Zaini; Mohd. Nor, Amir Husin; Samuri, Mohd Al-Adib (Canadian Center of Science and Education, 2015)
Study problems revolve around the emergence of social problems resulting from the fact that the wife goes out to work which leads to neglecting certain rights and obligations. Moreover, the cases of domestic violence by beatings and verbal abuse in all its forms increased. Accordingly, the importance of the study lies in building a happy family which is the first core in building a society; it is essential to protect its integrity and foundations, and also the role of maqasid shariah appears to be crucial in solving contemporary family problems. This study aims to highlight the rights and duties between spouses in accordance with Islamic law, and to identify the reasons and motivations that led to the existence of these problems and how to address them from the maqasid shariah perspective. The study adopted inductive and analytical approach by looking into schools of Islamic jurisprudence, and discussing the authorities relied on by the jurists to see the points of agreement and disagreement, and then the analysis of texts and issues in the light of maqasid shariah. The study found that the main reason for having family problems is lack of knowledge of the spouses of rights and duties and abiding by them. And wife’s work is permissible by the shariah within certain limits and restrictions and not to contradict maqasid shariah, and a working wife has to balance between her wok and the interest of her family.